Land, livelihood, and civility in southern Mexico : Oaxaca Valley communities in history - Cook, Scott, 1937- (Joe R. and Teresa Lozano Long series in Latin American and Latino art and culture., 2014)
Examines social relations, land ownership, and artisan trades in rural Oaxaca villages.